Relevansi Pupuh Durma Pada Mocoan Lontar Yusup dan Kultur Masyarakat Osing Banyuwangi - Handi Wiyono; E. W. Suprihatin; Hartono Hartono (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Banyuwangi is a district located on the eastern tip of Java Island which has a unique cultural diversity. This is reflected in the diverse arts. One of the arts in Banyuwangi is macapat which is called Mocoan. The most popular Mocoan performed by the Osing tribal community is the Mocoan Lontar Yusup where the literary work read tells the story of the prophet Yusuf. This art material, which is the focus of research, is studied and analyzed and its relevance is sought for the culture of the people who hold this culture.This study uses a qualitative approach and the data are presented descriptively. Using logical analogies, analyzed based on interactive techniques and based on arguments. Based on the data obtained, it was found that there is a special approach to the expression of the Banyuwangi macapat art, namely in text and song melodies. The special approach is that there are special terminology, meter rules and mining rules. The three data are relevant to the culture of the foreign community, namely exclusive, open, and bound.